Catena-Poly Tetrahydropyrimidine-4 1.72-Hydrate] - Sahin, O.; Büyuk̈güngör, O.; Köse, D.A.; Zümreoǧlu-Karan, B.; Necefoǧlu, H. (Int Union Crystallography, 2006)
The CoII ion in the title complex {[Co(C5H 2N2O4)(H2O)3]·1. 72H2O}n, has a distorted octahedral coordination geometry comprised of three water ligands, one deprotonated pyrimidine N atom and an adjacent carboxylate O atom of one orotate ligand. The sixth coordination site is occupied by an exocyclic O atom from a neighbouring orotate moiety, and through this interaction a helicoidal chain is formed. The molecules are linked by intramolecular Owater-H⋯O and intermolecular N-H⋯O and Owater-H⋯O hydrogen bonds, forming a three-dimensional network. © 2006 International Union of Crystallography.
[